Calling for a systems approach in microbiome research and innovation. (February 2022) - Meisner, Annelein; Wepner, Beatrix; Kostic, Tanja; van Overbeek, Leo S; Bunthof, Christine J; de Souza, Rafael Soares Correa; Olivares, Marta; Sanz, Yolanda; Lange, Lene; Fischer, Doreen; Sessitsch, Angela; Smidt, Hauke; et al.
Graphical abstract: Highlights: Microbiomes are deployed in health, food, environmental and industrial applications. Microbiomes are mostly studied within a single ecosystem or science discipline. Deployment of microbiome-based solutions has potential to increase sustainability. Research needs to transition to a systems approach to leverage microbiome functions. Abstract : Microbiomes are all around us in natural and cultivated ecosystems, for example, soils, plants, animals and our own body. Microbiomes are essential players of biotechnological applications, and their functions drive human, animal, plant and environmental health. The rapidly developing microbiome research landscape was studied by a global mapping excercise and bibliometric analysis. Although microbiome research is performed in many different science fields, using similar concepts within and across fields, microbiomes are mostly investigated one ecosystem at-a-time. In order to fully understand microbiome impacts and leverage microbial functions, research needs to adopt a systems approach connecting microbiomes and research initiatives in divergent fields to create understanding on how microbiomes can be modulated for desirable functions as a basis of sustainable, circular bioeconomy.